Numerical optimization of flow uniformity inside an under body- oval substrate to improve emissions of IC engines. Issue 3 (16th February 2016) - Om Ariara Guhan, C.P.; Arthanareeswaran, G.; Varadarajan, K.N.; Krishnan, S.
Abstract: Oval substrates are widely used in automobiles to reduce the exhaust emissions in Diesel oxidation Catalyst of CI engine. Because of constraints in space and packaging Oval substrate is preferred rather than round substrate. Obtaining the flow uniformity is very challenging in oval substrate comparing with round substrate. In this present work attempts are made to optimize the inlet cone design to achieve the optimal flow uniformity with the help of CATIA V5 which is 3D design tool and CFX which is 3D CFD tool. Initially length of inlet cone and mass flow rate of exhaust stream are analysed to understand the effects of flow uniformity and pressure drop. Then short straight cones and angled cones are designed. Angled cones have been designed by two methodologies. First methodology is rotating flow inlet plane along the substrate in shorter or longer axis. Second method is shifting the flow inlet plane along the longer axis. Large improvement in flow uniformity is observed when the flow inlet plane is shifted along the direction of longer axis by 10, 20 and 30 mm away from geometrical centre. When the inlet plane is rotated again based on 30 mm shifted geometry, significant improvement at rotation angle of 20° is observed. The flow uniformity is optimum when second shift is performed based on second rotation. This present work shows that for an oval substrate flow, uniformity index can be optimized when inlet cone is angled by rotation of flow inlet plane along axis of substrate.